Efek Beta Karoten dan Agregasi Klorofil Pada Fotostabilitas Klorofil a dalam Pelarut Aseton - Costa, Junet. F. da; Karwur, Ferry F; Limantara, Leenawaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
Chlorophyll as photosynthetic pigment has many benefits to human such as antioxidant, antibacterial, color additive,immunity, and photosensitizer. Concerning to these applications, chlorophyll a will react with oxygen and light andreduce its effectiveness. It is then important to understand the stability of chlorophyll a on oxygen and light.Stability of chlorophyll a in the presence of beta-carotene (1:1) in acetone was studied for various waterconcentrations. Each solution was exposed to red light (ë e” 630 nm) for 0.5; 1.0; 2.5; 5.0; 10; 20; 30; 40; 50; and 60minutes and their spectrum were analysed. When water was added (8.33; 16.67; 25; 33.33; 41.67; 50; 58.33; 66.67;75; and 83.33 percent) to the acetone solution of chlorophyll a, the chlorophylls aggregate, and in the presence ofbeta-carotene, the chlorophyll more stable. The water shifts the chlorophyll a spectrum toward red duringillumination with or without the presence of carotene. The formation of oligomeric chlorophyll a aggregate occurswithin 10-20 minutes after the water was applied. This strategy of aggregating the chlorophylls to dissipateexcess energy captured from light does not support the photostability of chlorophyll as much as beta-carotene.Surprisingly, when beta carotene was mixed with 66.7% and 75.0% of water, the chlorophyll a degraded 5.56% and9.71% respectively. In conclusion, the aggregate form of chlorophyll a and the presence of beta-carotene increasephotostability of chlorophyll a in acetone solution.